The Effect Of Underage Marriage Laws On The Status Of Children In The National Legal System - Yuganti Yuganti; Ferawati Royani; Sandi Aprianto (Utami Publisher, 2026)
Underhand marriage is a phenomenon that still occurs frequently in Indonesian society and has complex legal implications, particularly regarding the status of children born. Although these marriages are considered religiously valid, the lack of marriage registration results in a lack of administrative recognition by the state. This condition has a direct impact on determining the legal status of children in the national legal system, particularly regarding civil relations with parents, identity rights, and the fulfillment of other civil rights. This study aims to analyze the legal consequences of underhand marriages on the status of children born from a national legal perspective using a normative juridical approach. The analysis was conducted by examining relevant laws and regulations, legal doctrine, and court decisions, particularly Constitutional Court Decision Number 46/PUU-VIII/2010. This study also links these issues to the theories of legal certainty and legal protection. The results show that underhand marriages create uncertainty in the legal status of children because the recognition of the child's civil relationship with their biological father does not occur automatically but rather depends on subsequent legal mechanisms. From the perspective of legal certainty and legal protection, this condition places children in a vulnerable position and potentially experiences discrimination. Therefore, legal interpretation and policies are needed that are more oriented towards the best interests of children in order to guarantee certainty of status and fair legal protection.